Electrical isolation of the superior vena cava using second‐generation cryoballoon in patients with atrial fibrillation. (11th April 2020) - Wei, Hui‐Qiang; Guo, Xiao‐Gang; Sun, Qi; Yang, Jian‐Du; Xie, Hai‐Yang; Cao, Zhong‐Jing; Chen, Yan‐Qiao; Zhang, Shu; Wu, Shulin; Ma, Jian
Abstract: Background: The safety and efficacy of superior vena cava (SVC) isolation using second‐generation cryoballoon (CB) ablation remain unknown. Methods: A total of 26 (3.2%) patients with SVC‐related paroxysmal atrial fibrillation (AF) from a consecutive series of 806 patients who underwent second‐generation CB were included. Pulmonary vein isolation was initially achieved by CB ablation. If the SVC trigger was determined, the electrical isolation of SVC isolation was performed using the second‐generation CB. Results: Real‐time SVC potential was observed in all patients. Isolation of the SVC was successfully accomplished in 21 (80.8%) patients. The mean number of freeze cycles in each patient was 2.1 ± 1.1. The mean time to isolation and ablation duration were 22.5 ± 14.2 seconds and 94.5 ± 22.3 seconds, respectively. A transient phrenic nerve (PN) injury was observed in five patients (19.2%). There were two patients (7.7%) experienced reversible sinus node injury during the first application. During a mean follow‐up period of 13.2 ± 5.8 months, four patients (15.4%) had atrial arrhythmia recurrences. Conclusion: Isolation of SVC using the second‐generation 28‐mm CB is feasible when SVC driver during AF is identified. Vigilant monitoring of PN function during CB ablation of SVC is needed to avoid PN injury.